2020
DOI: 10.18203/2320-1770.ijrcog20202719
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of contraception complications among hospitalized women following self-induced medical abortion at tertiary hospital

Abstract: Background: Unwanted pregnancies in women and complications of induced abortions are an important health problem in the world. There is recent trend of self-induced medical abortion pill use over the counter without knowing the recommendations. Objectives of this study were to study socio demographic profile, presentations, management of hospitalized women for medical abortion related complications. To explore out contraceptive practices in those women. To way out the reasons for choosing medical abortion by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…( 27) Pal et al reported an 18.17% case fatality rate for septic abortions. (28) Keeping in view the catastrophic consequences of septic miscarriage, it is the need of the hour that necessary action, including the legalization of abortion, free availability of contraceptive services, and training of midwives and health professionals at the primary and secondary levels should be done to minimize associated morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…( 27) Pal et al reported an 18.17% case fatality rate for septic abortions. (28) Keeping in view the catastrophic consequences of septic miscarriage, it is the need of the hour that necessary action, including the legalization of abortion, free availability of contraceptive services, and training of midwives and health professionals at the primary and secondary levels should be done to minimize associated morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%